PENERAPAN ALGORITMA USER-BASED FILTERING DALAM MEMBERIKAN REKOMENDASI BARANG PADA TOKO BIN WAHAB - Sholikah Indrawati; Nur Nafi'iyah; Purnomo Hadi Susilo (Universitas Madura, 2020)
The goods recommendation system at Wahab Sugio Bin Shop is needed to help customers choose the items to be purchased. The purpose of this study is to make a product recommendation application according to the ranking of the selected product. The benefit is to make it easier for shop owners to display goods sold. The first step in the user based collaborative filteing algorithm is that the customer gives a rating of the product purchased, where the product is used as much as 6 researches. Next the system will calculate the average and find the similarity value between products with the adjusted cosine similarity statement. The results of the system similarity value will provide recommendations for products that can be purchased. The system recommendations show an accuracy of 98%, so it is good for use at Wahab Sugio's Bin Store.